Study and Research Paths to Improve Web-Based Inquiry Learning: Study Case of an ICT Course in Engineering - Andreu Moreno; Elena Bartolomé (MDPI AG, 2021)
Many active, inquiry-based learning activities nowadays rely upon the students' capacity to perform efficient information research on the Internet. Study and Research Paths (SRPs) have been proposed to model inquiry learning, and successfully used as teaching formats in different areas. In an SRP the search for an answer to a generating question (Q0) leads to a sequence of derived questions and answers, which are modeled using a Q-A map. We have investigated the benefits of using SRPs and Q-A maps to improve Web-based inquiry learning. We designed an SRP for a course on Information and Communication Technologies (ICT), belonging to an Engineering degree. The class-session SRPs revolved around Q0 questions such as 'What is a «firewall»?', 'What are the main features of 5G?' etc. Our results, based on the analysis of six courses conducted between 2015/16-2020/21, show that the SRP is an enriching tool for learning ICT: content expands beyond that of the traditional course and is maintained up-to-date. Students are engaged and motivated by the active-search activity. In addition, the SRP helps in improving the students' skills in searching and selecting information on the Internet. The Q-A maps served both the students, to structure their Web inquiry, and the teacher, to monitor the learning study process.